ВОССТАНОВЛЕНИЕ ГОЛОСА ПРИ РИНОЛАЛИИ - Гусейнова Н. Т. (World Science, 2018)
Voice disorders during rinophonia and rinolalia are different. Leading is the change in the tembre of voice - open nasalization - an unpleasant nasal resonance giving moreover, a blurred, dull sound of the whole speech. The nasalization occurs because there is no distinction between the nasal and oral cavities. It significantly changes the acoustic characteristics of phonemes. The voice becomes monotonous, complicated and weak. Cleft palate, as an anatomical defect of the extension tube, leads to asymmetry in the structure of the resonator cavities of the larynx, pharynx, nose, and also discoordinates the function of the palate-larynx complex, to which the palate plays the role of a triggering motor causative agent. It is proved that the position of the soft palate causes a change in the position of the vocal folds. That is why, disruption of integrity, anatomical and functional asymmetry of the muscles of the soft palate and pharynx lead with age to functional asymmetry of the vocal folds, which reduces the strength of the voice, makes it squashed, depleted, unmodulated.